2021
DOI: 10.3390/cells10113179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BCG Revaccination on Occupationally Exposed Medical Personnel Vaccinated against SARS-CoV-2

Abstract: The production of specific neutralizing antibodies by individuals is thought to be the best option for reducing the number of patients with severe COVID-19, which is the reason why multiple vaccines are currently being administered worldwide. We aimed to explore the effect of revaccination with BCG, on the response to a subsequent anti-SARS-CoV-2 vaccine, in persons occupationally exposed to COVID-19 patients. Two groups of 30 randomized participants were selected: one group received a BCG revaccination, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…Our data is consistent with previous work highlighting the benefit of prior or synchronous BCG vaccination in boosting heterologous vaccine responses 67 , including to a trivalent influenza vaccine 44 and to vaccination against pneumococcus, tetanus toxoid, measles, mumps, diphtheria and polio in BCG immunized infants [46][47][48] . Our data is also consistent with the results of the Mexican study which demonstrated prior BCG vaccination to enhance the Pfizer/Biotech induced NAb response,4 weeks after BCG vaccination 49 . In the context of COVID-19, BCG may not be unique and is consistent with emerging acceptance of the benefits of heterologous vaccination strategies.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Our data is consistent with previous work highlighting the benefit of prior or synchronous BCG vaccination in boosting heterologous vaccine responses 67 , including to a trivalent influenza vaccine 44 and to vaccination against pneumococcus, tetanus toxoid, measles, mumps, diphtheria and polio in BCG immunized infants [46][47][48] . Our data is also consistent with the results of the Mexican study which demonstrated prior BCG vaccination to enhance the Pfizer/Biotech induced NAb response,4 weeks after BCG vaccination 49 . In the context of COVID-19, BCG may not be unique and is consistent with emerging acceptance of the benefits of heterologous vaccination strategies.…”
supporting
confidence: 92%
“…Humoral responses to vaccination against pneumococcus, tetanus toxoid, measles, mumps, diphtheria, polio were higher in BCG immunized compared to non-BCG immunized infants in several trials [46][47][48] . Importantly, data from a randomized study in Mexico showed neutralizing antibody (NAb) titers induced by the Pfizer-BioNTech SARS-CoV-2 vaccine to be higher in the group that received BCG first and then the SARS-CoV-2 vaccine relative to the group that received placebo and SARS-CoV-2 vaccine 49 . In an animal study, human-ACE2 transgenic mice given BCG coupled with a trimeric-Spike vaccine generated a higher titer of NAb and a greater Th1 response than controls receiving trimeric-Spike vaccine alone and cleared infection with minimal immunopathology following SARS-CoV-2 challenge 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Such non-specific protection by BCG against non-mycobacterial infections and perhaps other non-infectious disorders include induction of: (i) a heterologous TH1, TH17, and CD8+ lymphocytic response and (ii) a non-specific memory in innate immune cells (natural killer cells, monocytes, and macrophages) through epigenetic effects and metabolic rewiring in a paradigm known as "trained immunity" [33]. Of contemporary note is the investigation of BCG in the COVID-19 pandemic; BCG benefit has been shown in both animal COVID-19 studies and humans where BCG demonstrated a "synergy" with COVID-19 vaccination [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“… Positive: Revaccination with BCG synergized with subsequent vaccination against SARS-CoV-2 in occupationally exposed personnel. [145] Clinical trial 695 health care workers in Poland No effect. Negative: The statistical analysis did not reveal any significant correlation between the frequency of incidents suspected of COVID-19 and BCG-10 vaccination, the result of the tuberculin test and the number of scars.…”
Section: Is the Bcg Vaccine Effective Against Sars-cov-2 Infection?mentioning
confidence: 99%